Diabetes management in clinical practice - Chowdhury, Tahseen A. (Springer London, 2014)
Diabetes Management in Clinical Practice provides a much-needed succinct overview of the advances in the management of diabetes and its complications. Using an evidence-based approach, the authors review relevant trials and discuss prospects for future therapies and avenues of research. Written by experts in the field for a global audience, Diabetes Management in Clinical Practice is a practical guide for diabetologists and endocrinologists, family practitioners, specialist nurses, dietitians and podiatrists.